Best Answer

3x = 2y + 3

3x -3 = 2y +3 -3

3x - 3 = 2y

(3x -3)/2 = 2y / 2

y = 1/2 x (3x - 3)

3x = 2y +3

3x - 3x = -3x +2y +3

0 = -3x +2y +3

-1 x (0) = -1 x (-3x +2y +3)

0 = 3x - 2y -3

Q: How do you write this equation 3x equals 2y plus 3 in function form?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

readuse the answer

Set of instruction are known as function.

0x2 + 1x - 7 = 0

dihydrogen monoxide. not positive though.

The slope of your quadratic equation in general form or standard form.

Related questions

4x + y = 10 is a perfectly valid functional form. The standard form is 4x + y - 10 = 0

you have to solve y to get the answer

Yes it is a function. In standard form it is y=x-4.

There are no "following" data!

Well, if you solve the equation for "y", you have "y" as a function of "x". Or you can do it the other way round; solve for "x", to get "x" as a function of "y" (the first option is more commonly used, though).

y=3x+12

y = (c - Ax) / (B)

It is the equation of a straight line

4

y=2/3x-7

y = -x + 8

f(x) = mx +b. m and b are arbitrary constants.